2009
DOI: 10.1590/s0100-29452009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência de argila silicatada no controle de Xanthomonas axonopodis pv. passiflorae, in vitro e em mudas de maracujazeiro-amarelo

Abstract: RESUMO-a mancha bacteriana do maracujá, causada pela bactéria Xanthomonas axonopodis pv. passiflorae, ocorre em todas as regiões produtoras do País, sendo responsável por grandes perdas econômicas na cultura do maracujazeiro-amarelo. O presente trabalho teve como objetivos testar a eficiência de argila silicatada na inibição da bactéria X. axonopodis pv. passiflorae in vitro e no controle preventivo e curativo da mancha bacteriana em mudas de maracujazeiro-amarelo. a argila silicatada foi adicionada ao meio de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
2
2
0
3
Order By: Relevance
“…In a previous study, Si enhanced the resistance to the coffee plant pathogen Cercospora coffeicola, with increase in cuticle thickness (POZZA et al, 2004). This increase is due mainly to the formation of a thicker layer of epicuticular wax, which hinders the penetration of the pathogen through the cuticle or stomata (POZZA et al, 2004;BRANCAGLIONE et al, 2009). It is possible that similar structures were induced in the lima bean leaves treated with calcium silicate in the present investigation, but further studies are needed to confirm this possibility.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…In a previous study, Si enhanced the resistance to the coffee plant pathogen Cercospora coffeicola, with increase in cuticle thickness (POZZA et al, 2004). This increase is due mainly to the formation of a thicker layer of epicuticular wax, which hinders the penetration of the pathogen through the cuticle or stomata (POZZA et al, 2004;BRANCAGLIONE et al, 2009). It is possible that similar structures were induced in the lima bean leaves treated with calcium silicate in the present investigation, but further studies are needed to confirm this possibility.…”
Section: Resultssupporting
confidence: 50%
“…2), achieving the lowest minimum value (0.7) among all treatments used on this sample. BRANCAGLIONE et al (2009) also found a significant effect of silicate clay on the preventive control of bacterial leaf spot (Xanthomonas axonopodis pv. Passiflorae) on seedlings of the yellow passion fruit plant (Passiflora edulis (Sims) f. flavicarpa (Deg.…”
Section: Resultsmentioning
confidence: 90%
“…Bentonite is used as fertilizer and have been cited in the literature as a promising product in controlling plant pathogens BRANCAGLIONE et al, 2009). However, we are not aware of any information on the activity of bentonite as an insecticide.…”
Section: Mortality Of S Frugiperda and S Eridania Fed On Plants Trementioning
confidence: 99%
“…Alguns pós de rocha podem ser encontrados no mercado, mas a maioria das formulações testadas em experimentos pertence a fontes locais. Um pó de rocha silicatada comercial foi testada por Branchaglione et al (2009) que verificaram resultados positivos no controle da bacteriose do maracujazeiro.…”
unclassified
“…O enxofre faz parte de algumas recomendações de controle da antracnose, muito embora não tenha registro para a cultura (PIO RIBEIRO; MARIANO, 1995) e, além disso, o elemento está relacionado com o aumento da produtividade dos pomares de maracujá (SANTOS et al, 2007). Ainda com relação a utilização de argila silicatada, Branchaglione et al (2009) recomendaram doses de 1,0 a 2,0% para controle da bacteriose em plantas de maracujazeiro.…”
unclassified